Transcriptional Regulations on the Low-Temperature-Induced Floral Transition in an Orchidaceae Species, Dendrobium nobile: An Expressed Sequence Tags Analysis. (9th April 2012) - Liang, Shan; Ye, Qing-Sheng; Li, Rui-Hong; Leng, Jia-Yi; Li, Mei-Ru; Wang, Xiao-Jing; Li, Hong-Qing
Abstract : Vernalization-induced flowering is a cold-relevant adaptation in many species, but little is known about the genetic basis behind in Orchidaceae species. Here, we reported a collection of 15017 expressed sequence tags (ESTs) from the vernalized axillary buds of an Orchidaceae species, Dendrobium nobile, which were assembled for 9616 unique gene clusters. Functional enrichment analysis showed that genes in relation to the responses to stresses, especially in the form of low temperatures, and those involving in protein biosynthesis and chromatin assembly were significantly overrepresented during 40 days of vernalization. Additionally, a total of 59 putative flowering-relevant genes were recognized, including those homologous to known key players in vernalization pathways in temperate cereals or Arabidopsis, such as cereal VRN1, FT/VRN3, and Arabidopsis AGL19 . Results from this study suggest that the networks regulating vernalization-induced floral transition are conserved, but just in a part, in D. nobile, temperate cereals, and Arabidopsis .